Structural reforms in the Eu : a simulation -based analysis using the QUEST model with endogenous growth - Roeger, Werner; Varga, Janos; Veld, Jan in't 1962-; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : Office for Infrastructures and Logistics in Brussels, 2008)
This paper describes the endogenous growth version of the QUEST III model and uses it to analyse the macroeconomic impact of various structural reform measures. This paper describes a micro-founded DSGE model with endogenous growth that is used to analyse the macroeconomic impact of structural reforms in Europe. The new QUEST III model is a useful tool for analysing the costs and benefits of reforms in terms of concrete and quantifiable policy measures, in particular fiscal policy instruments such as taxes, benefits, subsidies and education expenditures, administrative costs faced by firms and regulatory indices. Our results confirm the beneficial effects on output and employment of skill-biased tax reforms, measures that improve the skill composition of the labour force, R&D subsidies, raising competition in final goods market, increased financial market integration and measures that remove entry barriers in certain markets. The model also allows us to examine the adjustment path and the time lags involved before these benefits can be reaped.
Economic Papers.